2016
DOI: 10.1038/ncomms11915
|View full text |Cite
|
Sign up to set email alerts
|

Early synaptic deficits in the APP/PS1 mouse model of Alzheimer’s disease involve neuronal adenosine A2A receptors

Abstract: Synaptic plasticity in the autoassociative network of recurrent connections among hippocampal CA3 pyramidal cells is thought to enable the storage of episodic memory. Impaired episodic memory is an early manifestation of cognitive deficits in Alzheimer's disease (AD). In the APP/PS1 mouse model of AD amyloidosis, we show that associative long-term synaptic potentiation (LTP) is abolished in CA3 pyramidal cells at an early stage. This is caused by activation of upregulated neuronal adenosine A2A receptors (A2AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
204
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 199 publications
(234 citation statements)
references
References 55 publications
(82 reference statements)
19
204
1
1
Order By: Relevance
“…Additionally, CA3‐CA3 connections play an important role in the initial storage of memory . Disruptions of synaptic transmission in CA3‐CA3 lead to deficits in one‐trial learning and one‐trial memory . Our data on reduced neuronal populations in CA3 in adult F0 females probably are suggestive of disturbed plasticity in this hippocampal region, possibly owing to a reduction in the number of synapses or in dendritic arborization or other changes leading to less effective signal transmission, thereby in turn causing changes in the memory processes.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, CA3‐CA3 connections play an important role in the initial storage of memory . Disruptions of synaptic transmission in CA3‐CA3 lead to deficits in one‐trial learning and one‐trial memory . Our data on reduced neuronal populations in CA3 in adult F0 females probably are suggestive of disturbed plasticity in this hippocampal region, possibly owing to a reduction in the number of synapses or in dendritic arborization or other changes leading to less effective signal transmission, thereby in turn causing changes in the memory processes.…”
Section: Discussionmentioning
confidence: 66%
“…Several studies have previously shown that A 2A R blockade prevents memory deficits associated with chronic stress or depression (Batalha et al, ; Cunha et al, ; Kaster et al, ; Machado et al, ). These studies focused on the relation between synaptic dysfunction and memory deterioration and have shown that neuronal A 2A R were both necessary and sufficient to trigger memory deficits (Li et al, ; Pagnussat et al, ; Viana da Silva et al, ). Although the blockade of A 2A R is globally accepted as a cognitive enhancer and anxiolytic, in animal models of disease, the majority of the studies were performed in males or the gender was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with anxiety disorders commonly display cognitive impairment (Kendler et al, ; Tanokashira et al, ) and A 2A R blockade prevents cognitive deficits (Batalha et al, ; Cunha et al, ; Dall'Igna et al, ; Kaster et al, ; Li et al, ; Prediger et al, ; Viana da Silva et al, ), we now investigated if A 2A R blockade recovers cognition in females with anxiety resistant to A 2A R antagonism. We further assessed if A 2A R in the dorsal hippocampus (dHIP) and in the mPFC differently control microglia morphologic remodeling in these two brain regions, which process anxiety and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…memory formation (Shors and Matzel 1997, Malenka and Nicoll 1999, Bliim et al 2016. Furthermore, the fact that LTP deficit is a common theme observed in AD mouse models strengthens the link between LTP and memory deficits observed in both clinical and/or preclinical research (Gengler et al 2010, Sheng et al 2012, Webster et al 2014, Viana da Silva et al 2016). …”
Section: Introductionmentioning
confidence: 92%